2018
DOI: 10.1136/jclinpath-2017-204981
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic concordance of reporting lymphovascular invasion in breast cancer

Abstract: AimsThis study aims to assess the diagnostic agreement of lymphovascular invasion (LVI) in invasive breast cancer (BC).MethodsData on LVI were collected from the UK National Health Service Breast Screening Programme pathology external quality assurance scheme database. 101 BCs assessed over a 10-year period (2004–2014) were included. Cases were scored by an average of 600 pathologists. Three H&E staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, we were able to retrieve approximately 85% of LVI and PNI statuses. Further, pathological information for LVI and PNI was obtained from the original reports through TIES, and these reports were not validated or standardized [51]. Third, whereas TCGA has significant benefits, with a large amount of transcriptomic information associated with patient survival, it also has limitations, such as a relatively short follow-up duration, as well as no detailed information available for neoadjuvant or adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were able to retrieve approximately 85% of LVI and PNI statuses. Further, pathological information for LVI and PNI was obtained from the original reports through TIES, and these reports were not validated or standardized [51]. Third, whereas TCGA has significant benefits, with a large amount of transcriptomic information associated with patient survival, it also has limitations, such as a relatively short follow-up duration, as well as no detailed information available for neoadjuvant or adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with both an RS and N0 status, LVI was associated with worse OS in those with RS 11-25 (HR ¼ 1.31, 95% CI 1.09-1.57) and 26-100 (HR ¼ 1.58, 95% CI 1.30-1.93), but not RS 0-10 (HR ¼ 1.1, 95% CI 0.77-1.53), although there was no statistically significant interaction between LVI and RS. The authors concluded that while LVI did not predict chemotherapy benefit in those with intermediate RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), it did add prognostic information in ER-positive, HER2-negative, N0 BC with RS (11-100). 17 Both of these studies' findings further support those of the Trial Assigning Individualized Options for Treatment (TAILORX) study which, though did not evaluate LVI, similarly demonstrated that while patients with an intermediate-risk Oncotype DX score (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) did not receive an overall benefit from AC, certain patients (pre-menopausal with RS 16-25) could still derive some advantages, especially when high-risk clinical features such as tumor size and/or grade were present.…”
Section: Esmo Openmentioning
confidence: 99%
“…The authors concluded that while LVI did not predict chemotherapy benefit in those with intermediate RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), it did add prognostic information in ER-positive, HER2-negative, N0 BC with RS (11-100). 17 Both of these studies' findings further support those of the Trial Assigning Individualized Options for Treatment (TAILORX) study which, though did not evaluate LVI, similarly demonstrated that while patients with an intermediate-risk Oncotype DX score (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) did not receive an overall benefit from AC, certain patients (pre-menopausal with RS 16-25) could still derive some advantages, especially when high-risk clinical features such as tumor size and/or grade were present. 39,40 Taken together, the results of our own study and those of these studies evaluating RS suggest the existence of subgroups of patients with intermediate RS that may not normally receive AC but for whom other prognostic factors, LVI in particular, may indicate clinical benefit.…”
Section: Esmo Openmentioning
confidence: 99%
“…This precluded separate subgroup analyses for vascular and lymphatic invasion and highlights the need for pathologists to report these features separately to facilitate future studies and clearer risk stratification. It should also be noted that there is data to suggest that there may be significant inter‐observer variability between pathologists in the reporting of LVI in other solid organ cancers and specifically vascular invasion in follicular thyroid carcinoma 19–21 . To our knowledge, this has not been studied in PTC to date.…”
Section: Discussionmentioning
confidence: 94%